2007
DOI: 10.1161/01.str.0000259659.91505.40
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring After the Acute Stage of Stroke

Abstract: Background and Purposes-In the early stage of stroke, the occurrence of neurologic and medical complications is associated with clinical deterioration. Previous studies were focused on the first week after stroke onset. The aim of this study was to evaluate the impact of complications on clinical outcome in patients with stroke in the early subacute stage. Methods-We prospectively evaluated the influence on the outcome of complications feasible (MC) and not feasible for monitoring (NMC) in all patients with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 24 publications
(32 reference statements)
2
47
1
4
Order By: Relevance
“…The risks of most of the individual medical complications in our study were in agreement with those found in other studies. 2,6,7,10,12,15 We did, however, find a lower risk of falls (2.5%) and constipation (7.0%) than in most other studies, in which reported risks of falls have ranged from 8.4% to 25% 2,4,5,9,11 and risks of constipation ranged from 16% to 66%. 7,28 This difference may reflect that we only included patients treated in a stroke unit because the units are believed to be effective in preventing complications.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The risks of most of the individual medical complications in our study were in agreement with those found in other studies. 2,6,7,10,12,15 We did, however, find a lower risk of falls (2.5%) and constipation (7.0%) than in most other studies, in which reported risks of falls have ranged from 8.4% to 25% 2,4,5,9,11 and risks of constipation ranged from 16% to 66%. 7,28 This difference may reflect that we only included patients treated in a stroke unit because the units are believed to be effective in preventing complications.…”
Section: Discussioncontrasting
confidence: 90%
“…В ранее проведенных исследованиях было показано, что приблизительно у 96% всех пациентов, госпитализированных по пово-ду инсульта, развиваются общие или неврологические осложнения [2][3][4][5][6][7][8][9][10][11][12]. Несмотря на тот факт, что разви-тие осложнений может препятствовать оптимальному восстановлению и связано с повышенной летальнос-тью [2][3][4][5][6][7][9][10][11][12][13][14][15][16], данные о причинах развития ослож-нений редки и неубедительны [2,4,6,11,13].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Many of those complications are potentially preventable with the improvement of stroke care. This is best done in a dedicated stroke unit with experienced staff and early mobilization 12,13,14 . Pneumonia is the leading cause of death in the post-acute phase of stroke 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prognostic importance of body temperature during the acute phase of ischemic stroke has been increasingly recognized. Several clinical studies have consistently shown that in the early phase after stroke, fever (>37.5°C) is very common, occurring in up to 61 % of patients, increases with the severity of stroke, and is a strong predictor of an unfavorable outcome [25][26][27]. A multitude of different biochemical and inflammatory mechanisms responsible for the detrimental effects of fever during the acute phase of stroke have been identified, including 1) enhanced release of excitatory neurotransmitters; 2) increased metabolic demands; 3) exaggerated free oxygen radical production; 4) increased breakdown of the blood-brain barrier; 5) elevated rate of potentially damaging depolarizations in the ischemic penumbra; 6) impaired recovery of energy metabolism and enhanced inhibition of protein kinases; and 7) worsening of cytoskeletal proteolysis [28].…”
Section: Rationale Behind Prophylactic Antibiotic Therapy In Strokementioning
confidence: 99%